Is there any relationship between safety, health and productivity of labourers in the construction industry? - Paul, Elizabeth Varsha; Nagasubramaniyan, Dr. G. (The journal of contemporary issues in business and government, 2021)
Construction industry is the most hazardous as it is labour intensive in nature. Labourers suffer a lot due to hard labour and erogenous tasks. Hence health, safety and productivity is affected. This study tries to examine the relationship between health, safety and productivity. The respondents included contractors and labourers in various construction sites such as residential projects, irrigation infrastructures, industrial shed, and commercial buildings. A methodological triangulation such as questionnaires, semi- structured interviews and field visit were done. Using SPSS, multiple regression was used for the study. The major finding proved that health does not influence labour productivity and safety does influence labour productivity. The study concludes with major recommendations to be followed by the management.